Ap4 is rate limiting for intestinal tumor formation by controlling the homeostasis of intestinal stem cells - Stephanie Jaeckel (Nature Portfolio, 2018)
The c-MYC oncoprotein has many targets whose actions are not fully understood including TFAP4/AP4. Here, the authors show in a mouse model of inherited colorectal cancer that deletion of AP4 decreased the frequency of c-MYC-driven intestinal adenomas, and reveal Ap4 as a mediator of adenoma initiation and regulator of colonic and intestinal stem cell and Paneth cell homeostasis.